Islam And The Values Of Multicultural Da’wah: Concept And Social Practice - Mahya, Mimi Jamilah; Roro Sri Rejeki Waluyajati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Multiculturalism is an increasingly prominent phenomenon in global society, where individuals from various national, cultural, ethnic, religious, and linguistic backgrounds interact and influence one another. This makes multiculturalism one of the key characteristics of modern society. This study aims to explore the Islamic perspective on the concept of multicultural da’wah and how Islamic values can be applied within this context. The research method used is qualitative with a literature review approach, where data sources are drawn from various references relevant to the study of multiculturalism. The findings indicate that Islam offers principles and values that can serve as a guide in dealing with multiculturalism, such as the concept of Islamic universalism, maqasid al-shariah, love for fellow human beings, and the concept of ukhuwwah (brotherhood). These findings are expected to provide deeper insight into how Islamic teachings can contribute to creating a harmonious and inclusive society amidst diversity.